2020
DOI: 10.21203/rs.3.rs-29280/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catastrophic costs among tuberculosis patients in Zimbabwe: a national health facility-based survey

Abstract: Background: Tuberculosis (TB) has biological and socio-economic dimensions. The socio-economic impact of TB may plunge households into financial catastrophes. The End TB strategy seeks to mitigate socio-economic factors which may act as barriers to accessing TB services. Countries have been encouraged to provide baseline estimates of catastrophic costs by 2020. We sought to determine the prevalence, risk factors and major drivers of catastrophic costs among TB patients in Zimbabwe. Methods: We conducted a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…was not calculated as the heterogeneity was high. The proportion was variants, two studies reported similar proportions, Tomeny, 2020 [15] & Collins Timire, 2020 [47] with a proportion of 41% and 43% respectively. However, higher proportion 52% reported among Chittamany2020 [33] and Nhung, 2018 [37].…”
Section: Secondary Outcomementioning
confidence: 90%
See 2 more Smart Citations
“…was not calculated as the heterogeneity was high. The proportion was variants, two studies reported similar proportions, Tomeny, 2020 [15] & Collins Timire, 2020 [47] with a proportion of 41% and 43% respectively. However, higher proportion 52% reported among Chittamany2020 [33] and Nhung, 2018 [37].…”
Section: Secondary Outcomementioning
confidence: 90%
“…The proportion of the mean direct cost to the mean total cost at 20% addressed in 7 studies, ranged from 26% in Chittamany, 2020 [33] to 93% in Yang, 2020 [32]. Low proportions were observed in Fuady, 2018 [41], Tomeny, 2020 [15], and Collins Timire, 2020 [47] with proportion of 32%, 34% and 49% respectively, while high proportion also reported in Muttamba, 2020 [30], with 66% and in Nhung, 2018 [37] with 68%. The pooled proportion of mean direct to total cost was di cult to assess because of the heterogeneity which wasn't explained even after a meta-regression performed.…”
Section: Pooled Proportion Of Direct Cost In Mdrmentioning
confidence: 93%
See 1 more Smart Citation
“…2018 [41], Tomeny, 2020 [15], and Collins Timire, 2020 [47] with proportion of 32%, 34% and 49% respectively, while high proportion also reported in Muttamba, 2020 [30], with 66% and in Nhung, 2018 [37] with 68%. The pooled proportion of direct to total cost was difficult to assess because of the heterogeneity which wasn't explained even after a meta-regression performed.…”
Section: Pooled Proportion Of Direct Cost In Mdrmentioning
confidence: 94%
“…With 63% pooled proportion, 95%CI [40-80%], I 2 = 96%, three studies measured the CTP at 40% [12,29,30] and after the sensitivity test the heterogeneity was I 2= 0, while the pooled proportion increased to 70%, 95%CI [64-76%]. Among drug sensitive and drug resistant TB, the proportion of direct cost to the total cost ranged from (33% to 65%) [15,30,33,37,41,47] and (26%-93%) [15,30,32,33,37,41,47] respectively.…”
Section: Pooled Proportion Of Ctp At 40%mentioning
confidence: 99%